Individual and mutual effects of elevated carbon dioxide and temperature on salt and cadmium uptake and translocation by rice seedlings - Feng, Yu-Xi; Tian, Peng; Li, Cheng-Zhi; Zhang, Qing; Trapp, Stefan; Yu, Xiao-Zhang (Frontiers in Plant Science, 2023)
Plant kingdoms are facing increasingly harsh environmental challenges marked by the coexposure of salinity and pollution in the pedosphere and elevated CO2 and temperature in the atmosphere due to the rapid acceleration of industrialization and global climate change. In this study, we deployed a hydroponics-based experiment to explore the individual and mutual effects of different temperatures (low temperature, T1: 23°C; high temperature, T2: 27°C) and CO2 concentrations (ambient CO2: 360 ppm; medium CO2: 450 ppm; high CO2: 700 ppm) on the uptake and translocation of sodium chloride (NaCl, 0.0, 0.2, 0.6, and 1.1 g Na/L) and cadmium nitrate (Cd(NO3)2·4H2O, 0.0, 0.2, 1.8, and 5.4 mg Cd/L) by rice seedlings. The results indicated that Cd and Na exposure significantly (P< 0.05) inhibited plant growth, but T2 and medium/high CO2 alleviated the effects of Cd and Na on plant growth. Neither significant synergistic nor antagonistic effects of Cd and Na were observed, particularly not at T1 or high CO2. At increasing temperatures, relative growth rates increased despite higher concentrations of Cd and Na in both rice roots and shoots. Similarly, higher CO2 stimulated the growth rate but resulted in significantly lower concentrations of Na, while the Cd concentration was highest at medium CO2. Coexposure experiments suggested that the concentration of Cd in roots slightly declined with additional Na and more at T2. Overall, our preliminary study suggested that global climate change may alter the distribution of mineral and toxic elements in rice plants as well as the tolerance of the plants.